2022
DOI: 10.3389/fbioe.2022.962230
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive and rapid method of lead detection using nanoparticle technology based on monoclonal antibody

Abstract: Lead (Pb) threatens public health due to its toxicity and nonbiodegradable characteristics. It is of significance to develop a sensitive and rapid method for Pb detection. In this study, monoclonal antibodies against Pb were screened with a high affinity constant (Kaff) of 3.56 × 109 L/mol. Au nanosphere particles (AuNS) and Au nanoflower particles (AuNF) were synthesized with a diameter of 15 nm and 60 nm, respectively. The specific anti-Pb antibodies were then immobilized on AuNS and AuNF for probe developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Moreover, AuNF with a larger specific surface area could improve the immobilization yield of antibodies. Previous findings showed that the sensitivity of LFICS based on AuNF for the testing of lead (Pb) ions was improved ( Jia et al, 2022 ). Ji et al reported that AuNF with advanced optical and colloidal properties exhibited more sensitivity by 10 times than AuNP for AFB 1 detection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AuNF with a larger specific surface area could improve the immobilization yield of antibodies. Previous findings showed that the sensitivity of LFICS based on AuNF for the testing of lead (Pb) ions was improved ( Jia et al, 2022 ). Ji et al reported that AuNF with advanced optical and colloidal properties exhibited more sensitivity by 10 times than AuNP for AFB 1 detection.…”
Section: Introductionmentioning
confidence: 99%